2018
DOI: 10.1016/j.arabjc.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

One-pot three-component synthesis of peptidomimics for investigation of antibacterial and antineoplastic properties

Abstract: The a-hydroxyphosphonate generated from dialkyl phosphites and 1-phenyl-1H-pyrazole-4-carbaldehyde derivative was, in situ, trapped by isothiocyanates, isocyanates or acetic anhydride to produce dialkyl phosphorylmethyl-carbamothioates, -carbamates and/or -methyl acetates in good yields. The reactions were carried out in tetrahydrofuran (THF) in one step at room temperature, using K 2 CO 3 catalyst. Antimicrobial and antineoplastic activities of the synthesized compounds were estimated. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…α-Hydroxy phosphonates are recognized as a valuable class of substances exhibiting interesting medicinal and agricultural properties [ 1 , 2 , 3 , 4 ]. α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…α-Hydroxy phosphonates are recognized as a valuable class of substances exhibiting interesting medicinal and agricultural properties [ 1 , 2 , 3 , 4 ]. α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the foregoing considerations and as part of our pre-vious and on-going studies [48][49][50][51][52], we have designed a new se-ries of αaminophosphonates tagged with sulfisoxazole via MWI-assisted Kabachnik-Fields reaction. The synthesized compounds were thereafter tested in vitro for their antimicrobial activities (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, synthesis and applications of di-and monophosphonoantes as well as phosphonoamidate-substituted heterocycles are also known by our scientific work. [21][22][23][24][25][26][27] In a series of papers, Abdel-Aziz et al reported the synthesis and reactions of thiazolo[3,2-a]benzimidazoles with different nucleophiles. [28][29][30] In this investigation, we studied the reactions of E-3-(dimethylamino)-1-(3-methylbenzo[d]thiazolo[3,2-a]imidazol-2-yl)prop-2-en-1-one (1) and 1-(3-methylbenzo[d] thiazolo[3,2-a]imidazol-2-yl)ethanone (12) with trialkyl phosphites 2ac, dialkylphosphonates 6a-c, and tris(dialkylamino)phosphines 8a,b as well as the constitution of the products.…”
Section: Introductionmentioning
confidence: 99%